2019
DOI: 10.1111/aogs.13743
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and risk of cesarean section in women with induced labor at term—A Nordic register‐based study

Abstract: Introduction: Over the last decades, induction of labor has increased in many countries along with increasing maternal age. We assessed the effects of maternal age and labor induction on cesarean section at term among nulliparous and multiparous women without previous cesarean section. Material and methods:We performed a retrospective national registry-based study from Denmark, Finland, Iceland, Norway, and Sweden including 3 398 586 deliveries between 2000 and 2011. We investigated the impact of age on cesare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…The models highlight the importance of variables such as maternal age, maternal height, pre-pregnancy BMI, gestational age, weight gain during pregnancy, degree of meconium-stained amniotic uid, indicator for occurrence of premature rupture of membranes and fetal sex in determining the cesarean delivery when women failed the trial of labor. These results are consistent with the existing literature on the risk of cesarean delivery [16,[21][22][23]. Past studies also found gestational age of induced labor and induction methods were related to the incidence of cesarean [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…The models highlight the importance of variables such as maternal age, maternal height, pre-pregnancy BMI, gestational age, weight gain during pregnancy, degree of meconium-stained amniotic uid, indicator for occurrence of premature rupture of membranes and fetal sex in determining the cesarean delivery when women failed the trial of labor. These results are consistent with the existing literature on the risk of cesarean delivery [16,[21][22][23]. Past studies also found gestational age of induced labor and induction methods were related to the incidence of cesarean [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…The model highlight the importance of variables such as maternal age, maternal height, pre-pregnancy BMI, gestational age, weight gain during pregnancy, induction method, degree of meconium-stained amniotic uid, indicator for occurrence of premature rupture of membranes and male fetus in determining the cesarean delivery when women failed the trial of labor. These results are consistent with the existing literature on the risk of cesarean delivery [18,[24][25][26]. Past studies also found gestational age of induced labor and induction methods were related to the incidence of cesarean [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…With advances of blood transfusion, anesthesiology, diversification of surgical methods, improvement of surgical suture materials, cesarean section has become an effective treatment of maternal women [ [1,2]]. However, the risks of postoperative thrombosis, intraoperative bleeding, uterine rupture, and placenta previa of repregnancy after cesarean delivery are significantly higher than those of women delivered via vaginal delivery [3][4][5].…”
Section: Introductionmentioning
confidence: 99%